The Effectiveness of Using the Flipped Learning Strategy Using Pen Tablet in the Achievement and Motivation towards Mathematics among Tenth Grade Female Students in Wadi Al-Seer District - Amawi, Suha Mohammad; Alassaf, Hamzeh Abd alftah (Journal of Educational and Psychological Sciences, 2021)
This study aimed to identify the effectiveness of flipped learning strategy using pen tablet in the achievement and motivation towards mathematics among tenth grade female students in Wadi Al-Seer district. The study used a Quasi-experimental design, Where the study was applied to a sample of (93) female students from the tenth grade, it was divided into (48) female students in the experimental group and (45) female students in the control group. The experimental group was taught using a flipped learning strategy by activating the pen tablet, while the control group studied in the traditional way. The Study tools were used achievement test and Motivation scale for learning mathematics.The results of the study showed a statistically significant difference at the level of significance (α = 0.05) between the mean achievement of female students in mathematics in the two experimental and control groups on the post test for the benefit of the experimental group students who studied using the flipped learning strategy using the pen tablet, where the arithmetic mean reached (15.96) of (20), The results also showed a statistically significant difference at the level of significance (α = 0.05) in the scores of the motivation scale towards mathematics between the experimental and control groups on the dimensional scale in favor of the experimental group students who studied using the flipped learning strategy using the pen tablet, where the arithmetic mean reached (2.89) From (3.) the differences were in favor of the experimental group.In light of the results of the study; it recommends the use of the flipped learning strategy by activating the pen tablet tool in teaching math for the tenth grade, and further research into the use of the pen tablet in teaching other educational materials and for other educational stages.
Keywords: Pen Tablet; Flipped Learning; Achievement; Motivation; Mathematics; Tenth Grade